Structural and morphological study of nanostructured n-type silicon - Hadi, Hasan A. (Iraqi Journal of Physics, 2012)
In this study, investigations of structural properties of n-type porous silicon prepared by laser assisted-electrochemical etching were demonstrated. The Photo- electrochemical Etching technique, (PEC) was used to produce porous silicon for n-type with orientation of (111). X-ray diffraction studies showed distinct variations between the fresh silicon surface and the synthesized porous silicon surfaces. Atomic force microscopy (AFM) analysis was used to study the morphology of porous silicon layer. AFM results showed that root mean square (RMS) of roughness and the grain size of porous silicon decreased as etching current density increased. The chemical bonding and structure were investigated by using fourier transformation infrared spectroscopy (FTIR). Porosity of the porous silicon layer and thickness were determined gravimetrically. Increasing the etching current density led to increase the surface porosity and thickness. Porosity between77% and 82% were observed for current densities between 24 mA/cm2 and 116 mA/cm2